LEAD-FREE Cu-Zn ALLOY, ALLOY PRODUCT MANUFACTURED THEREFROM, AND PROCESS FOR MANUFACTURING ALLOY PRODUCT FROM THAT ALLOY
A controlled Cu-Zn alloy composition with balanced phases and limited impurities addresses unpredictable interactions, providing high wear resistance and cold formability for sliding shoes in articulated joints, ensuring strength and cost-effectiveness.
Patent Information
- Application Number
- JP2024079219
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-17
- Filing Date
- 2024-05-15
- Publication Date
- 2024-12-27
AI Technical Summary
Existing Cu-Zn alloys face unpredictable changes due to complex interactions among multiple alloying elements, affecting properties like wear resistance, cold formability, and strength, especially when subjected to sliding stresses in oil environments, which are critical for components like sliding shoes in articulated joints.
A Cu-Zn alloy with a controlled composition of Cu, Si, Mn, Ni, Fe, P, Cr, Al, Sn, and Zn, with limited impurities, forming a structure with finely distributed silicides and a balanced phase proportion, ensuring high wear resistance, cold formability, and strength, without the need for special processing steps.
The alloy achieves high wear resistance, cold formability, and sufficient strength for sliding shoes in articulated joints, meeting complex requirements without excessive hardness, and allows for cost-effective production with improved machinability and fatigue resistance.
Smart Images

Figure 2024180781000006 
Figure 2024180781000007 
Figure 2024180781000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a lead-free Cu-Zn alloy and to alloy products made from the alloy. The present subject matter also includes a method of making the alloy products. [Background technology]
[0002] High-tensile brass alloys with several different alloy compositions are known from the prior art. These alloys are used for different purposes. In addition to the main elements Cu and Zn, high-tensile brass alloys contain other elements that allow the adjustment of the desired alloy properties. This also includes the structure that can be achieved thereby. The structure of the alloy product is largely responsible for the specific properties of the alloy product, for example its processability, such as hot forming. For hot forming, it is preferred that the brass alloy has a predominant β phase. The main reasons for the good hot formability of the β phase at high temperatures are the easier activation of the sliding system in the microstructure of the alloy as a carrier of plastic deformation, and the low level of hot hardening. In simple terms, this leads to a higher ductility and lower hardness of the β phase during hot forming. A certain proportion of the α phase is tolerated. However, efforts are being made to avoid the formation of the γ phase in hot-formable high-tensile brass alloys, since this phase is brittle and therefore has a negative effect on the desired hot forming properties.
[0003] The problem with multi-component alloys, especially those containing several alloying elements in addition to Cu and Zn, is that changes in a single component can lead to unpredictable changes in the alloy product due to the complex interactions between the individual alloying components. Further changes in several alloying components in the alloy will lead to unpredictable results.
[0004] For components subject to sliding stresses, low-lead or lead-free Cu-Zn alloys with phase precipitates in the form of manganese silicides have been proposed. These precipitates provide the alloy product with high resistance to abrasive wear and reduce the tendency for localized adhesion to the sliding surfaces. Such alloys often have a structure with a predominantly β phase, or a heterogeneous matrix with α and β phases.
[0005] However, a high proportion of β phase has a negative effect on the cold formability of Cu-Zn alloys. To address this issue, DE102007029991B4 proposes forming an alloy product having a structure with an α matrix in which iron- and nickel-containing manganese silicides are present and 5% by volume to 50% by volume of β phase is embedded. The alloy composition is 28-36% by weight zinc, 0.5-1.5% by weight silicon, 1.5-2.5% by weight manganese, 0.2-1.0% by weight nickel, 0.5-1.5% by weight aluminum, 0.1-1.0% by weight iron, and the remainder is copper.
[0006] Furthermore, EP 3272888 A1 discloses a brass alloy product which allows a high degree of cold forming without intermediate annealing. An alloy composition of 21-27 wt.% zinc, 0.2-0.8 wt.% silicon, 1.1-1.9 wt.% manganese and 0.005-0.2 wt.% phosphorus results in an alpha matrix in which manganese-containing phosphides are present in a nacreous arrangement.
[0007] DE 3626435 A1 discloses a Cu-Zn alloy having 66-90% by weight copper, 1.5-8.0% by weight manganese, 0.3-7.0% by weight aluminium, 0.3-2.0% by weight phosphorus, the remainder being zinc. At a sufficiently high proportion of aluminium, the manganese phosphides acting as wear reducers are substantially present in a eutectic distribution within the alpha matrix, which is smaller than the predominantly precipitated phosphides and therefore does not adversely affect cold formability.
[0008] WO2015 / 046421A1 discloses a tarnish-insensitive copper alloy having 17-34 wt% Zn, 0.005-1.8 wt% Al, 0.01-1.5 wt% Mn, 0.01-5 wt% Ni, 0.01-1.0 wt% Si, 0.005-0.9 wt% P, 0.01-2.5 wt% Zn, 0.0005-0.0030 wt% Pb, and the balance being copper. The structure of this alloy is dominated by the α phase, with small proportions of β and γ phases. The application area of this alloy is color stability.
[0009] Another previously known Cu-Zn alloy with high wear and corrosion resistance is known from JPS62274036A. This alloy has the following composition (in weight percent): Cu 37.7-89.7%, Si 0.05-3.0%, Mn 0.1-6.0%, P 0.005-0.10%, Al 0.05-1.0% and Sn: 0.05-1.0%, balance Zn. Ni, Fe, Cr and / or Pb can be added to the alloy as essential alloying elements in proportions of 0.005-2.0% by weight.
[0010] Furthermore, alloy products made from lead-free Cu-Zn alloy are known from EP 3992319 A1. This previously known alloy or alloy products made therefrom are characterized by special phase precipitation for a wide process window with simplified preparation. Furthermore, this previously known alloy product has good corrosion resistance and good machinability.
[0011] The requirements for Cu-Zn alloys or alloy products made therefrom can be very complex. A particularly complex requirement profile for Cu-Zn alloys or alloy products made therefrom exists when they are designed to be subjected to sliding stresses in an oil environment, through which lateral forces are introduced by dynamic loads into the sliding surface. Such applications of sliding parts, typically designed as sliding shoes, arise, for example, when the sliding part is part of an articulated joint, for example a ball joint, and forms part of an articulated joint that receives a swivel head as a joint partner of another part. The requirements imposed on such parts concern not only special wear resistance and compatibility with lubricants (even when using different lubricants, especially lubricants with additives), but also sufficient fatigue strength and sufficient plastic deformation reserve to avoid stress fractures. If the articulated joint, especially when embodied as a ball joint, is part of an axial piston machine, such as an axial piston pump or an axial piston motor, which axial piston machine is typically designed as a swash plate or tilting shaft, there are also corresponding requirements for the sole of the sliding shoe, which is supported on a swash plate and moves by adjustment of the swash plate relative to it. In addition, good machinability and formability characteristics as well as sufficiently high strength are required. Additionally, the alloy must be inexpensive to manufacture. Summary of the Invention
[0012] The present invention is therefore based on the object of proposing a Cu-Zn alloy suitable for the manufacture of such products.
[0013] According to the invention, the object is a Cu-Zn alloy having (in % by weight): Cu: 60.5-65.6% Silicon: 1.1 to 1.7% Mn: 2.51-2.9% Ni: 0.15~0.55% Fe: 0.02 to 0.12% P: 0.26-0.39% Cr: 0.018~0.12% Al: max. 0.3% Sn: max. 0.3% Pb: max. 0.1% Zn: remainder This is achieved by a Cu-Zn alloy having not more than 0.1% per element and not more than 0.3% in total of unavoidable impurities.
[0014] This alloy meets complex requirements in order to make it possible to produce alloy products which meet a complex requirement profile, in particular that required for sliding shoes as part of articulated joints in oil environments.
[0015] The fact that this alloy also meets a complex requirement profile is due to the special interplay of the elements involved in the structure of the alloy, especially the special Mn, P and Cr content in combination with the Si content, as well as the small contribution of other elements to the structure of the alloy. The percentage of Fe is intentionally kept very low. The Si content is limited to a narrow range. By limiting the Fe and Si contents, silicides are formed as hard phases, but not excessively. Taking into account the P content of the alloy, the percentage of Fe is also kept low so that too coarse iron phosphates are not formed. With the claimed Si content, silicides are formed as hard phases in percentages of not more than 3-6% by volume. A higher percentage of silicides improves the wear resistance of the alloy products, for example used as sliding shoes as parts of articulated joints, but under certain circumstances increases the wear of the surfaces of the swivel heads interacting with it, which is undesirable in such applications. The silicides are typically present in two fractions, namely a coarser fraction adjusted to the press direction and with a grain size of 15-20 μm. The second fraction, a relatively large number of finely divided silicides, is mainly responsible for the wear resistance. These finely divided silicides have a grain size of up to 1 μm and are found in the β phase, which is uniformly distributed in the structure. The proportion of β phase in the alloy according to the invention is 17-30%.
[0016] The Si content is adjusted with respect to the alloying proportions of other silicide-forming elements so that a certain proportion of free Si remains in the matrix. This has a favorable effect on the formation of a passivation layer when the alloy product is used in an oil environment, especially an oil environment containing additives or synthetic low-friction oils. In this high-tensile brass alloy, Mn, together with Cu and Zn, is an essential element in terms of its proportion. Mn increases strength. However, it has been shown that a higher Mn content leads to a reduction in the elongation at break. Therefore, the Mn content is limited to a maximum of 2.9% by weight. The elements Al and Sn, which are typically essential alloying components in conventional alloys of this type, are not used in this Cu-Zn alloy, but are allowed up to a maximum proportion of 0.3% by weight. Typically, the maximum proportion of the elements Al and Sn is 0.1% by weight. In conventional high-tensile brass alloys, Al is used alone or together with Ni in significantly higher proportions than are allowed in this high-tensile brass alloy to achieve the desired high strength. It was even more surprising that with the claimed Cu-Zn alloy the required strength was achieved even though no Al was involved and even though Ni only played a minor part in the alloy's structure.
[0017] It should also be emphasized that the alloy according to the invention has only a relatively small number of essential alloying elements, which simplifies the processability and reduces the ingress of contamination due to casting carry-over. With a Cu-Zn alloy having such a simple alloy structure, it could not be expected that this alloy or alloy products produced therefrom would still meet the very complex requirement profile as required for sliding parts such as sliding shoes as part of articulated joints.
[0018] This alloy can be produced inexpensively. An alloy is considered inexpensive if its Cu content is kept low and the requirements to be achieved by the alloy are achieved using cheaper accessory elements. This can be expressed by the Zn equivalent with the Guillet factor. In this way, the Cu content of the alloy can be limited. Preferably, Cu contributes to the structure of the alloy not more than 64% by weight.
[0019] The peculiarity of this alloy is that no special steps need to be taken when producing the alloy product, and the alloy product or the alloy product produced from the alloy product has sufficient hardness for the mentioned purpose, yield strength and tensile strength that meet the requirements, and still has sufficient elongation at break. For example, to meet the required profile of a sliding shoe as a part of an articulated joint, maximum values of yield strength, tensile strength and hardness are not desirable, since in such a case the alloy product does not have sufficient fatigue strength in the case of dynamic loading. Elongation at break A of at least 11% 5 Meets the relevant requirements. Breaking elongation A 5 is typically 8-15%.
[0020] Moreover, the alloy has sufficient cold formability to allow extruded rods produced as preliminary products to be cold drawn, which can enhance the mechanical properties. Furthermore, the cold drawing process improves the straightness of the rod, which is a plus for subsequent shaping machining processes. The cold formability of the alloy can also be used to allow the cold forming of all or part of the alloy products produced therefrom, for example, the ball head of a ball joint can be enclosed in a complementary ball joint receptacle by suitable flanging of the upper edge portion of the ball joint receptacle.
[0021] Interestingly, this alloy also has good machinability. The phosphides formed in the structure due to the P and Cr contents facilitate machining. The strength properties of the alloy or of the alloy products produced therefrom are not selected to be so high that the joint partners can adjust or work during the initial operating phase. Moreover, this alloy meets the requirement of sufficient relaxation strength. Wear resistance is provided by the hard phases formed as a result of the alloy composition, in particular the silicides uniformly distributed in the structure. A proportion of hard phases or of intermetallic phases between 2 and 6% by volume in the structure ensures wear resistance. Furthermore, the structure of this alloy or of the alloy products produced therefrom is dominated by the α phase. This structure typically contains only 10 to 30% by volume of the β phase. In addition to the hard phases, the remainder of the structure is formed by the α phase, and further phases with a proportion of up to 2% by volume, preferably less than 1% by volume, can be present at minor levels that do not affect the properties of the alloy. These include, among others, finer structural components that are not visible under an optical microscope, typically precipitates with a size of less than 1 μm.
[0022] The reserve for plastic deformation, and therefore for safety against failure of a component due to fatigue, can be expressed by the yield-to-tensile strength ratio. Thus, the yield-to-tensile strength ratio R p 0.2 / R m The bending fatigue strength is more than 185 MPa in the alloy according to the present invention, which is essential for the alloy or alloy product. 7 A duty cycle of 1000 times is used. The electrical conductivity of the alloy according to the invention is 9-16 mS / m.
[0023] The fine grain structure of the claimed alloy should also be emphasized. A sufficiently fine grain structure has a positive effect on the relaxation resistance, strength, especially fatigue strength, other mechanical properties, surface quality and machining properties. All of these factors favor a fine grain structure. The hardness HBW of the finished product ranges from 160 to 190, with an upper limit of preferably HBW 210.
[0024] Although the above-mentioned positive attributes of this Cu-Zn alloy can be observed over the entire range of elements participating in the alloy structure, the complex requirements profile imposed on this alloy is limited to the following alloy composition (wt.%): Cu: 60.5-65.5% Silicon: 1.15 to 1.6% Mn: 2.58-2.78% Ni: 0.2-0.5% Fe: 0.03 to 0.11% P: 0.26-0.39% Cr: 0.025~0.095% Al: max. 0.1% Sn: Max 0.1% Pb: max. 0.1% Zn: remainder This is further clarified by the inclusion of 0.1% per element and 0.3% in total of unavoidable impurities.
[0025] In particular, the alloy has the following composition (by weight): Cu: 62-64.2% Silicon: 1.15 to 1.6% Mn: 2.58-2.78% Ni: 0.25~0.45% Fe: 0.035 to 0.095% P: 0.26-0.39% Cr: 0.025~0.095% Al: max. 0.1% Sn: Max 0.1% Pb: max. 0.1% Zn: remainder together with incidental impurities not exceeding 0.1% per element and not exceeding 0.3% in total.
[0026] In particular, the alloy has the following composition (by weight): Cu: 62.5-64% Silicon: 1.25 to 1.5% Mn: 2.58-2.78% Ni: 0.25~0.45% Fe: 0.04 to 0.09% P: 0.26-0.39% Cr: 0.025~0.095% Al: max. 0.1% Sn: Max 0.1% Pb: max. 0.1% Zn: remainder together with incidental impurities not exceeding 0.1% per element and not exceeding 0.3% in total.
[0027] In particular, the alloy has the following composition: Cu: 63-63.5% Silicon: 1.3 to 1.4% Mn: 2.6-2.7% Ni: 0.3-0.4% Fe: 0.05 to 0.08% P: 0.3 to 0.35% Cr: 0.05~0.08% Al: max. 0.1% Sn: Max 0.1% Pb: max. 0.1% Zn: rest, together with incidental impurities not exceeding 0.1% per element and not exceeding 0.3% in total.
[0028] In a preferred exemplary embodiment, inevitable impurities are more narrowly permitted, specified to not exceed 0.05% per element and 0.2% in total.
[0029] The alloy or alloy product is generally manufactured using common process steps. This means that no special process steps need to be used to achieve the desired alloy properties. The alloy can be manufactured as follows: In a first step, the alloy is cast at a casting temperature of preferably 980°C to 1,100°C, preferably 1,000°C to 1,050°C. The alloy casting is then extruded in a temperature window of 720°C to 780°C, preferably 730°C to 760°C. A round rod is typically extruded. In the next step, the extruded rod is cold drawn. In this cold drawn state, the rod as a semi-finished product for manufacturing alloy products, for example a sliding shoe as a part of an articulated joint, has its highest mechanical strength values, but a relatively low breaking elongation. These first process steps are common steps for manufacturing semi-finished products from which actual high tensile brass alloy products are manufactured.
[0030] For the production of alloy products, a forging can also be used as the starting product. It can then be annealed (heat treated). If necessary, after the heat treatment step, for example in the case of plates, an intermediate step must be carried out to straighten the forged alloy product if its flatness deviates too much from the specifications. The alloy product is then annealed (heat treated) again. The alloy product can also be cold formed for other purposes after the forging step, for example for embossing purposes, and then annealed for relaxation. Forged parts have the same advantages as alloy products produced from extruded rod sections.
[0031] After cold drawing, in order to adjust the special characteristic strength values, the cold drawn rod straightened by cold drawing is thermally relaxed for 180-280 minutes in the temperature window of 380 ° C - 420 ° C, followed by cooling in ambient air. The above information concerns the implementation of this method in a chamber furnace. In a continuous oven, the same result can be achieved in a shorter time, in only 20-30 minutes. This slightly reduces the strength achieved by cold drawing in terms of yield strength, tensile strength and hardness, but at the same time significantly increases the relatively low breaking elongation of the cold drawn rod. The fact that it is achieved to the required degree by such a heat treatment is due to the special alloy composition. This heat treatment is also responsible for the formation of fine grain silicides, already mentioned above. The mechanical properties of the rod achieved in this way not only meet the requirement profile of the sliding shoe produced as an alloy product as a part of an articulated joint, but also meet the requirement profile (especially its machinability) for the further processing of this rod as a semi-finished product to produce the desired alloy product.
[0032] The mechanical properties after the final heat treatment of the extruded and subsequently cold drawn rods with a 20% reduction in cross-sectional area and therefore in the cross-sectional area of the finished product are in the range of values specified below: Yield strength Rp0.2: 430-560MPa, especially 430-500MPa Tensile strength Rm: 570-670MPa, especially 570-630MPa Breaking elongation A 5 : 8-11%, and Hardness: HBW 165~205, especially 165~195.
[0033] Mechanical properties are sensitive to cold forming. If the alloy product has lower mechanical properties, cold forming is performed with less forming, for example only 10%.
[0034] After such a rod section is cut to length, it is machined to the desired shape, for example the shape of a sliding shoe as part of an articulated joint. If the alloy product is a sliding shoe as part of an articulated joint, it is provided with an outer and inner contour and therefore also with the formation of a swivel head mount into which the swivel head of the joint partner is inserted, for example as part of a piston. The increase in the breaking elongation caused by the heat treatment makes it possible to plastically cold deform the alloy product so that it can surround the swivel head inserted in a form-fitting manner in the swivel head mount. For this purpose, the swivel head mount of the sliding shoe is preferably embodied with a height such that it overlaps with the apex of the swivel head. For the form-fitting connection of these two joint partners, the lip area of the swivel head mount can then be cold formed, for example flanged, so that it not only extends over the swivel head with respect to its height but also physically forms an undercut, so that the swivel head is captured in a form-fitting manner in the swivel head mount. This cold deformation of the lip area of the swivel head mount has the advantage that no additional parts are required for the necessary connection of the two joint partners. Moreover, the lip area of the swivel head mount is subjected to cold hardening as a result of this plastic cold deformation, so that the formed part or parts of the lip area of the swivel head mount advantageously increase the resistance moment as a swivel head enclosure, so that the swivel head accommodated therein is held firmly in the swivel head mount even under dynamic loads. Also, due to this cold hardening, less material is required to provide the above-mentioned swivel head enclosure. Such an arrangement is therefore particularly suitable for applications that require little space.
[0035] The claimed alloy is lead-free. A maximum Pb content of 0.1% by weight is permitted.
[0036] A study was carried out on Cu-Zn alloys according to the invention and the results were compared with those of comparative alloys.
[0037] The samples investigated were prepared as follows: Each alloy was cast at a temperature of -1,010°C. The casting was carried out as a vertical continuous cast with a diameter of 290 mm; - extruding the alloy casting at a temperature of about 745 ° C (the extruded rod (solid material) has a diameter of 36.5 mm); - cold drawing the extruded rod to obtain a 20% shape relative to the cross-sectional area of the extruded rod; - heat treating the cold drawn rod at about 395°C for 220 minutes, followed by cooling in air; -Cutting the specimens to length; -Performing various tests on cut samples to determine different property values.
[0038] Table 1 below shows the alloy compositions of the samples tested, where samples 1-6 are Cu-Zn alloys according to the invention and samples 7-12 are comparative alloys. TIFF2024180781000001.tif76170
[0039] The alloy according to the invention has a hard phase fraction of 4.5 to 5.5%.
[0040] Overall, the yield strength Rp0.2, tensile strength Rm, and breaking elongation A of the specimen in the compressed state (after extrusion) 5 Mechanical properties such as yield to tensile strength ratio (quotient of yield strength Rp0.2 to tensile strength Rm) and hardness HBW have been determined in the final state after cold drawing and after heat treatment. In addition, the structure of the final state of the specimens (finished products), which reflects the information of fatigue strength of dynamic cyclic loading components, as well as machinability, relaxation strength and bending fatigue strength were investigated. The results determined for the individual specimens are shown in Table 2.
[0041] The results of the finished samples examined can be found in Table 2 below. The information on machinability, relaxed strength and matrix fine grain size should be considered as a comparative study and for each purpose The sample marked with TIFF2024180781000002.tif3170 is sufficient, but the sample marked with Θ does not meet the relevant requirements. TIFF2024180781000003.tif96170
[0042] Specimens were also produced from the same alloy and cold stretched with only 10% forming. The mechanical properties determined for these specimens are given below. TIFF2024180781000004.tif96170
[0043] A specimen with a continuous casting diameter of 18 mm and a forming of 20% was also analyzed from the same alloy according to the invention. The strength values in this respect are, as expected, higher than those of the above specimen with an extruded rod diameter of 36.5 mm. These values are shown in the table below. TIFF2024180781000005.tif70170
[0044] The bending fatigue strength is measured at a specified stress of 10 7 The test was based on a load cycle of 1000 cycles.
[0045] A comparison of the test results of the samples according to the invention (samples 1-6) with alloy compositions not according to the invention (7-12) shows that the latter do not meet the requirements of at least one of the investigated properties. With regard to the bending fatigue strength, the requirement is met if the samples are subjected to a load cycle with a stress of 170 MPa or more and no damage can be detected. According to the information in the above table, the samples made from the alloys according to the invention have a higher bending fatigue strength. Elongation at break A 5 The requirement for is 10% to 14%, so comparative samples with too low or too high elongation at break do not meet the relevant requirement. With regard to the yield to tensile strength ratio, a sample meets the requirement if it is at least 66% but not more than 83%. These differences are due to the different alloy composition compared to the alloy composition according to the invention, since all samples were prepared using the same method.
[0046] All samples except samples 9 and 12 have sufficient lubricant compatibility and are therefore suitable for use in different oil environments without exhibiting excessive sensitivity and therefore increased wear.
[0047] If a forged semi-finished product is produced by hot forging after providing an alloy casting, comparable test results are achieved as shown above for an alloy product according to the invention which is extruded and then cold formed after providing an alloy casting. The forged semi-finished product can be a plate. The forged semi-finished product is then thermally relaxed, i.e. within a temperature window of 380°C to 430°C, for 160 to 320 minutes. The thermal relaxation is preferably carried out at about 385°C for 220 minutes. This thermal relaxation can be carried out in a continuous furnace. After the thermal relaxation, it is cooled in stationary or moving ambient air. Finally, the alloy product (forged semi-finished product) is shaped by machining.
[0048] Exemplary embodiments of alloy products according to the invention designed as sliding shoes are described below with reference to the accompanying drawings, in which: FIG. [Brief description of the drawings]
[0049] [Figure 1] FIG. 2 is a schematic cross-sectional view through an articulated joint between a sliding shoe with a swivel head mount and a swivel head of a joint partner inserted therein, prior to the form-fit connection of the two joint partners. [Diagram 2] After forming a form-fit connection between the two joint partners. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0050] FIG. 1 shows a ball joint 1. This ball joint 1 is a part of an axial piston pump designed as a swash plate or tilt axis pump. The ball joint 1 comprises a sliding shoe 2. The sliding shoe 2 is supported by its sole S on the swash plate Ss. The sliding shoe 2 can move relative to the swash plate Ss in the plane of its surface. The sliding shoe 2 was manufactured from the alloy of sample 4. After an extruded and heat treated rod piece was cut to length as a semi-finished product or preliminary product, this rod piece was machined to the shape shown in cross section in FIG. 2. In the exemplary embodiment shown in the figure, this was done by dry or wet machining, for example turning. The sliding shoe 2 is rotationally symmetrical. As part of this machining, a swivel head holder 3 was also inserted into the semi-finished product. The bottom of the swivel head mount 3 is hemispherical in shape and fits the lateral curvature of the swivel head 4 of the joint partner 5 inserted in the swivel head mount 3. The swivel head 4 is a ball head. The joint partner 5 is a piston, onto which the swivel head 4 is moulded. The height 6 of the swivel head mount 3 is dimensioned so that it projects beyond the apex 7 of the swivel head mount 4 starting from the bottom of the swivel head mount 3. In this part projecting beyond the apex 7, the swivel head mount 3 is initially cylindrical on the inside so that the swivel head 4 can be inserted therein to manufacture the ball joint 1. In the illustration of FIG. 1, the swivel head 4 is not yet form-fittingly connected to the sliding shoe 2.
[0051] The form-fit connection of the two partners of the ball joint 1 is shown in Figure 2. This figure also shows the mobility of the swivel head 4 relative to the sliding shoe 2 and the mobility of the sliding shoe 2 relative to the swash plate Ss.
[0052] For the form-fit connection between the sliding shoe 2 and the swivel head 4, the cold deformability provided by the heat treatment of the extrusion rod is used, and the lip area 8 of the swivel head mount 3 is formed radially towards the swivel head 4. The result of this cold forming is shown in FIG. 2. The lip area 8 of the swivel head mount 3 is formed so as to form an undercut that extends over the apex 7 of the swivel head 4. As a result of this cold forming, the lip area 8 has undergone cold hardening, so that it is harder than the other components of the sliding shoe 2. This cold hardening has the advantage that the physical extension over the apex 7 by the forming process does not have to be too great, in order to ensure a safe enclosure of the swivel head 4 within the swivel head mount 3, which is closed by the formation of an undercut as a result of forming.
[0053] The present invention has been described in the context of exemplary embodiments. There are many other possibilities for those skilled in the art to implement the invention without the need for more detailed explanations in the context of these descriptions, without departing from the scope of the present claims. [Explanation of symbols]
[0054] 1 Ball joint 2 Sliding shoe 3 Swivel head mount 4 Swivel Head 5. Joint Partners 6 Swivel head mount height 7. Top of the Turn 8 Mouth area S Sole Ss Swivel Plate
Claims
1. A Cu-Zn alloy comprising (in weight percent): Cu: 60.5-65.5% Si: 1.1-1.7% Mn: 2.51-2.9% Ni: 0.15-0.55% Fe:0.02~0.12% P: 0.26-0.39% Cr: 0.018-0.12% Al: maximum 0.3% Sn: maximum 0.3% Pb: max. 0.1% Zn: remainder together with unavoidable impurities not exceeding 0.1% per element and not exceeding 0.3% in total.
2. More specific contents (by weight) of the following alloying elements: Si: 1.15-1.6% Mn: 2.58-2.78% Ni: 0.2-0.5% Fe:0.03~0.11% Cr: 0.025-0.095% 2. The alloy of claim 1 having the formula:
3. More specific contents (by weight) of the following alloying elements: Cu: 62-64.2% Ni: 0.25-0.45% Fe: 0.035-0.095% 3. The alloy of claim 2 having the formula:
4. More specific contents (by weight) of the following alloying elements: Cu: 62.5-64% Si: 1.25-1.5% Fe:0.04~0.09% 4. The alloy of claim 3 having the formula:
5. More specific contents (by weight) of the following alloying elements: Cu: 63-63.5% Si: 1.3-1.4% Mn: 2.6-2.7% Ni: 0.3-0.4% Fe: 0.05-0.08% P: 0.3-0.35% Cr: 0.05-0.08% 5. The alloy of claim 4 having the following formula:
6. 6. An alloy according to any one of claims 1 to 5, characterized in that the structure of the alloy in the final state has 15 to 40% β-phase, 1.5 to 5.5% hard phases and the balance α-phase, with unavoidable further phases having a maximum proportion of 2%.
7. 7. The alloy according to claim 6, characterized in that the proportion of β phase is 15-30%, in particular 15-25%, and the proportion of hard phase is 2.5-3.5%.
8. The alloy product produced from the Cu—Zn alloy has the following mechanical properties in the final state: Yield strength Rp0.2: 300-560MPa Tensile strength Rm: 480 to 650 MPa Breaking elongation A 5 : 8-25% Hardness: HBW 140-205 8. The alloy according to claim 1 , characterized in that it has
9. The alloy product produced from the Cu—Zn alloy has the following mechanical properties in the final state: Yield strength Rp0.2: 300-450MPa Tensile strength Rm: 480 to 550 MPa Breaking elongation A 5 : 8-18% Hardness: HBWm 140-170 9. The alloy of claim 8 having
10. An alloy product manufactured from an alloy according to any one of claims 1 to 9, characterized in that it is a sliding shoe (2) manufactured from an extruded rod by machining.
11. 11. The alloy product according to claim 10, characterized in that the sliding shoe (2) is connected to the swivel head (4) in a form-fitting manner and is therefore part of a joint, and in that the sliding shoe (2) has a swivel head mount (3) and the swivel head (4) is inserted therein and held therein in a form-fitting manner so as to be movable relative to the sliding shoe (2), the form-fitting connection being provided by cold deformation of a lip region (8) of the swivel head mount (3) which extends at least in a region above the swivel head (4).
12. 12. The alloy product according to claim 11, characterized in that the sliding shoe (2) is designed as a ball joint with a swivel head (4) inserted in its swivel head mount (3).
13. 10. A method for producing an alloy product from the alloy of any one of claims 1 to 9, comprising the steps of: - providing an alloy casting; - extruding the rod at a temperature between 720°C and 780°C, in particular at about 745°C; - cold forming the extruded rod by stretching with a deformation of between 10 and 24%, based on the cross-sectional area of the rod obtained by cold forming relative to the initial cross-sectional area of the rod; - a thermal relaxation step of the cold-formed rod for 160 to 320 minutes in a temperature window between 380°C and 430°C, in particular for 220 minutes at about 395°C, which can be carried out in a continuous furnace, followed by a cooling step in stationary or moving ambient air; and - shaping the alloy product by machining sections cut to length from the thermally relaxed rod; A method comprising:
14. 10. A method for producing an alloy product from the alloy of any one of claims 1 to 9, comprising the steps of: - providing an alloy casting; - hot forging to produce a forged semi-finished product, - thermal relaxation of the forged semi-finished product within a temperature window of 380°C to 430°C for 160 to 320 minutes, in particular at about 395°C for 220 minutes, which can be carried out in a continuous furnace, followed by a cooling step in stationary or moving ambient air; and - The process of shaping alloy products by machining A method comprising:
15. 15. The method according to claim 14, characterized in that the thermal relaxation step is followed by a step of straightening the forged semi-finished product, the straightening step being followed by a heat treatment, typically with the same parameters as the thermal relaxation step.
16. A method according to any one of claims 13 to 15, characterised in that the alloy is cast at a temperature between 980°C and 1,100°C, preferably between 1,000°C and 1,050°C.
17. 17. Use of an alloy product manufactured by the method according to any one of claims 13 to 16, characterized in that the alloy product is used as part of a joint, a swivel head mount (3) is produced by machining and a swivel head (4) is inserted therein, and then a lip area (8) of the swivel head mount (3) is cold-formed in the circumferential direction at least in a region, so that the cold-formed lip area (8) extends in a form-fitting manner over the swivel head (4), thereby forming a form-fitting connection through which the swivel head (4) is movably held in the swivel head mount (3) of the alloy product.
18. 18. Use according to claim 17, characterised in that the lip area is flanged to form a form-fit connection of the swivel head and the alloy product.